A meta-analysis and trial sequential analysis of high intensity focused ultrasound ablation combined with transhepatic arterial chemotherapy and embolization for hepatoma - Zhang, Liang; Xu, Kuishuai; Zhang, Xuehui; Li, Linqian; Chong, Jing; Yu, Ning (Frontiers in Oncology, 2022)
Objective: The efficacy of High Intensity Focused Ultrasound Ablation(HIFU) combined with Transhepatic Arterial Chemotherapy And Embolization(TACE) versus TACE alone in the treatment of hepatoma was evaluated by meta-analysis and trial sequential analyses(TSA). Methods: Pubmed, Cochrane, Embase, Web of Science, Scoups and CNKI(China National Knowledge Infrastructure) databases were searched from database construction to April 2022, and observational studies and randomized controlled trials were included. Revman and Stata software were used for meta-analysis of tumor changes, survival rate, laboratory indicators and adverse reactions in the included studies, and TSA0.9 was used for sequential analysis. Results: Sixteen studies were included with a sample size of 1278 cases. Meta-analysis showed that the tumor response rate in the combined treatment group was 1.876 times higher than that in TACE alone (OR: 2.876, 95%CI: 2.145-3.856), and the 6-month to 5-year survival rate was 1-3 times higher, with statistically significant differences (P<0.05). Subgroup analysis showed that country, pathological type and study type were the sources of heterogeneity. Egger results showed that there was no publication bias (95%CI-1.410, 2.486, Ppublication=0.561), and the sensitivity analysis results were reliable. TSA results suggest that there may be false positive results, which need to be further confirmed by more studies. Conclusion: HIFU combined with TACE has better efficacy in the treatment of hepatoma, which is worthy of promotion. However, there may be false positive results in this study, which needs to be further verified by more extensive and more tests.